THROMBOPHILIA AND INTENSITY OF THE INTRAVASCULAR MICROCOAGULATION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE, ATHEROTHROMBOSIS - E. A. Shelest; A. E. Shuganov; L. I. Patrushev; I. N. Bokarev (Рациональная фармакотерапия в кардиологии)
Aim. To study the intensity of the intravascular microcoagulation in patients with atherothrombosis (AT), chronic obstructive pulmonary disease (COPD) and thrombophilia.Material and methods. 115 patients were enrolled into the study: 37 patients with COPD (22 with thrombophilia and 15 without thrombophilia); 37 patients with AT (23 with thrombophilia and 14 without thrombophilia); 41 patients with COPD+AT (24 with thrombophilia and 17 without thrombophilia). In the control group 53 healthy people (39 with thrombophilia and 14 without thrombophilia) were included. Median age was 62 (56.5, 69) years. The intensity of intravascular microcoagulation was measured: platelet factor 4 (PF4) by ELISA, D-dimer by ELISA, XIIa-dependent fibrinolysis (time). Polymerase chain reaction was used for detection of such trombophilia parameters as Leiden mutation, prothrombin gene mutation 20210A, mutation in the gene of methylenetetrahydrofolate reductase (MTHFR) and plasminogen activator inhibitor-1 (PAI-1).Results. The level of PF4 and D-dimer was significantly higher while fibrinolytic activity was lower in COPD (103.5 ME/ml, 70 ng/ml, 650 s, respectively), AT (127.1 ME/ml, 96,9 ng/ml, 850 s, respectively) and COPD+AT (136.5 ME/ml, 106.5 ng/ml, 1148 s, respectively) groups as compared with the control group (p<0.05). When analyzing the level of intravascular coagulation parameters in patients with thrombophilia and without it, levels of PF4, D-dimer and XIIa-dependent fibrinolysis (time) were significantly higher in thrombophilia subgroups among all patients (p<0.05). In patients with thrombophilia levels of these parameters were significantly higher in those with two or more thrombophilia gene polymorphisms than with one (p<0.01).Conclusion. The intensity of intravascular microcoagulation increases in patients with thrombophilia, atherothrombosis and COPD.